1980
DOI: 10.1002/1097-0142(19800501)45:9<2265::aid-cncr2820450908>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bleomycin and adriamycin with and without radiation in the treatment of inoperable esophageal cancer. A randomized study

Abstract: In a prospective randomized study, 31 patients with inoperable esophageal cancer were treated with a combination of bleomycin and adriamycin, and with a combination of these cytostatics and radiation. Evaluation of treatment results showed 3 partial remissions and 2 stable-disease cases in the group of 16 patients treated by cytostatic drugs alone; in all other cases, the disease progressed. The response rate achieved in this group was 19%. In the group including 15 patients who were irradiated with a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Recently, Kolaric et al (1980) reported good results of radiotherapy combined with relatively heavy chemotherapy using Bleomycin and Adriamycin. Byfield et al (1980) also described good results of infusional 5-fluorouracil and radiotherapy for non-resectable esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kolaric et al (1980) reported good results of radiotherapy combined with relatively heavy chemotherapy using Bleomycin and Adriamycin. Byfield et al (1980) also described good results of infusional 5-fluorouracil and radiotherapy for non-resectable esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Kolaric and coworkers compared efficacy of bleomycin, Adriamycin ® , and bleomycin/Adriamycin ® combination alone and each in combination with radiotherapy. 5,6,21 The multimodality regimens gave overall and complete response rates superior to those of chemotherapy-alone arms in these trials. The bleomycin/Adriamycin ® two-drug regimen disappointingly gave no advantage over results obtained by bleomycin or Adriamycin ® in combination with radiotherapy.…”
Section: Combined Modality Treatmentmentioning
confidence: 97%
“…However, bleomycin/cis-platinum and bleomycin/Adriamycin ® combinations gave 19 percent response rates each in 58 and 16 patients respectively and showed no advantage over the single-agent activity reported with these antitumor agents. 20,21 Bleomycin/methotrexate combination, on the other hand, resulted in one complete and three partial responses in five patients. 5 The three-drug combination bleomycin/cis-platinum/vinde-sine has been evaluated at Memorial Sloan-Kettering Cancer Center and given encouraging results.…”
Section: Multidrug Combination Chemotherapymentioning
confidence: 97%
“…Another type of comparison has been made in two randomized trials by Kolaric et al (38,123). CT alone has been compared with CT (doxorubicin + bleomycin or doxorubicin alone) given concurrent with RT showing significantly better response rates when combined therapy was used (38,123).…”
Section: Chemoradiotherapy Without Surgerymentioning
confidence: 99%
“…CT alone has been compared with CT (doxorubicin + bleomycin or doxorubicin alone) given concurrent with RT showing significantly better response rates when combined therapy was used (38,123). In a first study the response rate was 33% vs 60% for doxorubicin and doxorubicin + RT (45-52 Gy, 2 Gy/fraction) respectively (123) and in a second study doxorubicin + bleomycin gave a response rate of 19% and doxorubicin + bleomycin + RT (36-40 Gy, 2 Gy/fraction) a 60% response rate (38).…”
Section: Chemoradiotherapy Without Surgerymentioning
confidence: 99%